The Brand Trust As The Impact Of The Service Recovery Of The International Fast Food Restaurant - Muhammad Daffa Lazuardi; Popy Rufaidah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the influence of service recovery on brand trust among international fast-food restaurant customers in Bandung City. The service recovery variable encompasses distributive justice, procedural justice, and interactional justice. In contrast, the brand trust variable comprises two dimensions: fiability and intentionality. This study employs primary data gathered through an online survey of 215 respondents who are consumers of international fast-food restaurants and have experienced inappropriate service with an international fast-food chain outlet. The proposed hypothesis was tested using structural equation modeling (SEM). Based on the results of R-squared tests, path coefficient analysis, and SMARTPLS 3.0 software measurements, service recovery significantly and positively impacts brand trust for customers of international fast-food restaurants in Bandung City.